Fodor's Southern California 2024 - Bell, Carrie; Crabtree, Cheryl; Kast-Myers, Marlise; Mangin, Daniel (Fodor's Travel, a division of Internet Brands, Inc., 2024)
Whether you want to wander the Hollywood Walk of Fame in Los Angeles, lounge poolside in Palm Springs, or marvel at the San Diego Zoo, the local Fodors travel experts in Southern California are here to help! Fodors Southern California guidebook is packed with maps, carefully curated recommendations, and everything else you need to simplify your trip-planning process and make the most of your time.